Modular nanotransporters: a versatile approach for enhancing nuclear delivery and cytotoxicity of Auger electron-emitting (125)I - Slastnikova, Tatiana A (Springer, 2012)
BACKGROUND: This study evaluates the potential utility of a modular nanotransporter (MNT) for enhancing the nuclear delivery and cytotoxicity of the Auger electron emitter (125)I in cancer cells that overexpress the epidermal growth factor receptor (EGFR). METHODS: MNTs are recombinant multifunctional polypeptides that we have developed for achieving selective delivery of short-range therapeutics into cancer cells. MNTs contain functional modules for receptor binding, internalization, endosomal escape and nuclear translocation, thereby facilitating the transport of drugs from the cell surface to the nucleus. The MNT described herein utilized EGF as the targeting ligand and was labeled with (125)I using N-succinimidyl-4-guanidinomethyl-3-[(125)I]iodobenzoate (SGMIB). Membrane binding, intracellular and nuclear accumulation kinetics, and clonogenic survival assays were performed using the EGFR-expressing A431 epidermoid carcinoma and D247 MG glioma cell lines. RESULTS: [(125)I]SGMIB-MNT bound to A431 and D247 MG cells with an affinity comparable to that of native EGF. More than 60% of internalized [(125)I]SGMIB-MNT radioactivity accumulated in the cell nuclei after a 1-h incubation. The cytotoxic effectiveness of [(125)I]SGMIB-MNT compared with (125)I-labeled bovine serum albumin control was enhanced by a factor of 60 for D247 MG cells and more than 1,000-fold for A431 cells, which express higher levels of EGFR. CONCLUSIONS: MNT can be utilized to deliver (125)I into the nuclei of cancer cells overexpressing EGFR, significantly enhancing cytotoxicity. Further evaluation of [(125)I]SGMIB-MNT as a targeted radiotherapeutic for EGFR-expressing cancer cells appears warranted.